The role of undifferentiated connective tissue diseases in the development of ischemic-cervical insufficiency in pregnant women - O. M. Nosenko; Kamel Bakary (Kazimierz Wielki University, 2018)
The article analyzes clinical and anamnestic and biochemical markers of undifferentiated connective tissue diseases (UCTDs), the course of pregnancy and childbirth in 56 women with ischemic-cervical insufficiency (ICI) and 30 healthy pregnancies without ICI. The obtained data on the study of UCTDs point to its importance in the development of ICI along with other factors. The presence of pathology of connective tissue in the examined pregnant women can be assumed on the following factors: the pregravidar low Vargue index, the presence of phenotypic markers, diseases indicative of the presence of UCTDs, and the increase in the level of hydroxyproline in daily urine. Given the history of the particular pregnant woman, as well as the presence of markers of UCTDs, it is possible to predict the development of ICI with high probability. The findings indicate the need to examine women at high risk, with a threat or with miscarriage with the help of UCTDs markers, with the aim of taking measures for additional timely diagnosis and subsequent correction of ICI.